Preparation and Degradation Phenol Characterization of Ti/SnO2–Sb–Mo Electrode Doped with Different Contents of Molybdenum. Issue 5 (May 2015) - Liang, Jiyan; Geng, Cong; Li, Dan; Cui, Li; Wang, Xin
Abstract : The Ti/SnO2 –Sb–Mo electrodes doped with different molar ratios of molybdenum (Mo) were prepared by sol–gel method in order to investigate the effect of Mo on the characterization of Ti/SnO2 –Sb–Mo electrodes. X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), energy dispersive spectrometry (EDS), and linear scanning voltammetry (LSV) were used to scrutinize the coating material and the electrochemical activity. The concentration of phenol, the value of total organic carbon (TOC), the mineralization current efficiency (MCE) and the ultraviolet–visible spectroscopy (UV–Vis) spectrum of phenol solution were measured over the electrochemical degradation process of phenol to confirm the phenol degradation characterization of Ti/SnO2 –Sb–Mo electrodes. Results showed that the electrode at the Mo content of 1 at.% provided optimal catalytic activity for phenol degradation and the longest life time. The removal percentage of phenol and TOC were 99.62% and 82.67%, respectively. The Ti/SnO2 –Sb–Mo electrode with 1 at.% of Mo reached maximum MCE of phenol oxidation. The kinetic investigation of phenol and TOC degradation displayed the pseudo-first order reaction model. The Ti/SnO2 –Sb–Mo electrode coating with 7 at.% Mo presented the highest oxygen evolution overpotential, indicating the diverse effects for different Mo molar ratio doping.